Electronic components
By forming the interface of the electrode and resin electrode layer of the electronic component, the diffusion layer of copper oxide and silver is formed, and the problem of insufficient terminal electrode junction intensity is solved, and the effect of high junction reliability and low resistance is achieved.
Patent Information
- Application Number
- CN202110521575.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-07
- Filing Date
- 2021-05-13
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-05-13
AI Technical Summary
In the prior art, the bonding strength of the terminal electrodes is insufficient, resulting in an increase in contact resistance, affecting the reliability and performance of electronic components.
A resin electrode layer of the electrode parts and the vintage containing metal containing copper components and the resin electrode layer of the electrode part and silver containing silver containing silver containing silver. By forming a diffusion layer containing copper oxide and silver in the interface of the electrode and resin electrode layer, the joint reliability is improved and the joint reliability is Reduce resistance.
Achieve high coexistence and low resistance of terminal electrodes, and improves the overall performance and reliability of electronic components.
Smart Images

Figure CN113674968B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electronic component having terminal electrodes. Background Art
[0002] As shown in Patent Document 1, there is known an electronic component having terminal electrodes (sometimes also referred to as external electrodes) formed on the outer surface of an element body. In this electronic component, the terminal electrodes are connected to internal electrodes provided in the element body or extraction electrodes such as leads.
[0003] Such terminal electrodes can be formed by, for example, applying a sintering paste containing metal powder and glass components to the outer surface of the element body and sintering the portion to which the paste is applied at a temperature of about 700° C. or higher, as shown in Patent Document 1. However, when the terminal electrodes are formed by sintering at a high temperature as described above, defects such as cracks may occur in the element body due to the influence of thermal stress.
[0004] In addition, Patent Document 2 discloses a method for forming a terminal electrode using a thermosetting paste containing metal powder and a thermosetting resin. In this case, when forming the terminal electrode, a heating treatment can be performed at the curing temperature of the resin, and a sintering treatment at a high temperature is not required. However, in the terminal electrode of Patent Document 2, there are technical problems such as insufficient bonding strength with respect to the lead-out electrode and increased contact resistance of the bonding portion.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2013-045926
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 6-267784 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The present invention has been made in view of such actual circumstances, and an object of the present invention is to provide an electronic component in which the bonding reliability of terminal electrodes is high and the terminal electrodes have low resistance.
[0011] Technical solutions to solve problems
[0012] In order to achieve the above-mentioned object, the electronic component of the present invention has:
[0013] The lead-out electrode portion is provided on the outer surface of the element body;
[0014] a resin electrode layer formed on a portion of the outer surface of the element body and connected to the lead-out electrode portion;
[0015] The lead electrode portion contains copper as a main component,
[0016] The resin electrode layer comprises a silver-containing conductor powder and a resin,
[0017] A diffusion layer containing copper oxide and silver is formed at an interface between the extraction electrode portion and the resin electrode layer.
[0018] With the above-mentioned structure, the electronic component of the present invention can sufficiently ensure the bonding reliability between the extraction electrode portion and the terminal electrode (resin electrode layer), and can also achieve a lower resistance of the terminal electrode.
[0019] The diffusion layer may have a thickness of at least 30 nm. The diffusion layer may be identified as a region where a silver concentration gradient occurs from the outermost surface of the extraction electrode portion toward the resin electrode layer.
[0020] Preferably, the conductive powder of the resin electrode layer is composed of first particles with a particle size of micrometer order and second particles with a particle size of nanometer order. Since the resin electrode layer has the above structure, the bonding reliability of the terminal electrode is further improved and the resistance value of the terminal electrode can be further reduced.
[0021] Preferably, the first particles are flat, and the second particles are aggregated between the first particles.
[0022] With the above structure, the second particles electrically connect the first particles to each other, and the resistance value of the terminal electrode can be further reduced.
[0023] The diffusion layer may be present intermittently along an interface between the extraction electrode portion and the resin electrode layer.
[0024] In addition, an oxide film mainly containing copper oxide may be formed on the surface side of the lead-out electrode portion. In this case, the diffusion layer is located between the oxide film and the resin electrode layer. In the electronic component of the present invention, even if there is an oxide film on the surface side of the lead-out electrode portion, a diffusion layer is formed between the lead-out electrode portion and the resin electrode. Therefore, the bonding strength of the terminal electrode can be fully ensured, and the resistance value of the terminal electrode can also be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a perspective view showing an electronic component according to one embodiment of the present invention.
[0026] Figure 2 Viewed from the mounting surface Figure 1 A perspective view of the electronic components shown.
[0027] Figure 3A It is along Figure 1 A cross-sectional view taken along line IIIA-IIIA is shown.
[0028] Figure 3B Yes means Figure 1 and Figure 3A A cross-sectional view of a modified example of the electronic component shown.
[0029] Figure 4A It is a cross-sectional view showing a joining portion between a lead electrode portion and a terminal electrode.
[0030] Figure 4B Is magnification Figure 4A A cross-sectional view of region IVB is shown.
[0031] Figure 4C Is magnification Figure 4B A cross-sectional view of region IVC is shown.
[0032] Figure 4D Yes means Figure 4C A cross-sectional view of a modified example of .
[0033] Figure 5A This is a cross-sectional view showing a junction between a lead electrode portion and a terminal electrode in a conventional electronic component.
[0034] Figure 5B Is magnification Figure 5A A cross-sectional view of region VB is shown.
[0035] Fig. 6A Yes Figure 4C The results of line analysis of the interface between the lead electrode portion and the terminal electrode are shown.
[0036] Figure 6B Yes Figure 4D The results of line analysis of the interface between the lead electrode portion and the terminal electrode are shown.
[0037] Figure 7 Yes Figure 5B The results of line analysis of the boundary surface between the lead electrode portion and the terminal electrode are shown.
[0038] Fig. 8A Yes Figure 4C Mapping image of Ag in the cross section shown.
[0039] Figure 8B Yes Figure 4C Mapping image of Cu in cross section is shown.
[0040] Figure 8C Yes Figure 4C Mapping image of O in cross section shown. DETAILED DESCRIPTION
[0041] Hereinafter, the present invention will be described in detail based on the embodiments shown in the drawings.
[0042] like Figure 1 As shown in FIG. 1 , an inductor 2 as an electronic component according to a first embodiment of the present invention includes an element body 4 having a substantially rectangular parallelepiped shape (substantially hexahedron).
[0043] The component body 4 has an upper surface 4a, a bottom surface 4b located on the opposite side of the upper surface 4a in the Z-axis direction, and four side surfaces 4c to 4f. The size of the component body 4 is not particularly limited. For example, the size of the component body 4 in the X-axis direction can be set to 1.2 to 6.5 mm, the size in the Y-axis direction can be set to 0.6 to 6.5 mm, and the size in the height (Z-axis) direction can be set to 0.5 to 5.0 mm.
[0044] like Figure 1 and Figure 2 As shown, a pair of terminal electrodes 8 are formed on the bottom surface 4b of the element body 4. The pair of terminal electrodes 8 are formed separately in the X-axis direction and insulated from each other. In the inductor 2 of this embodiment, the terminal electrodes 8 can be connected to an external circuit via wiring, etc., which is not shown. In addition, the inductor 2 can be mounted on various substrates such as a circuit board using a bonding member such as solder or a conductive adhesive. When mounted on a substrate, the bottom surface 4b of the element body 4 becomes a mounting surface, and the terminal electrodes 8 and the substrate are bonded by a bonding member.
[0045] The element body 4 has a coil portion 6α therein. The coil portion 6α is formed by winding a winding wire 6 as a conductor into a coil shape. Figure 1 In the embodiment, the coil portion 6α is an air-core coil wound in a normal manner, but the winding method of the winding 6 is not limited to this. For example, the winding 6 may be an air-core coil wound in an α-direction or an air-core coil wound in an edge direction. Alternatively, the winding 6 may be directly wound on the winding core portion 41b described later (see Figure 3A ).
[0046] The winding 6 constituting the coil portion 6α is composed of a conductor portion mainly containing copper and an insulating layer covering the periphery of the conductor portion. More specifically, the conductor portion is composed of pure copper such as oxygen-free copper or tough copper, phosphor bronze, brass, red copper, beryllium copper, or an alloy containing copper such as a silver-copper alloy, or a copper-coated steel wire. On the other hand, the insulating layer only needs to have electrical insulation properties, and there are no particular restrictions. For example, epoxy resin, acrylic resin, polyurethane, polyimide, polyamide-imide, polyester, nylon, polyester, etc., or a synthetic resin obtained by mixing at least two of the above resins are exemplified. In addition, in the present embodiment, as Figure 1 and Figure 3AAs shown, the winding 6 is a round wire, and the cross-sectional shape of the conductor portion is a circle.
[0047] like Figure 1 and Figure 3A As shown in FIG. 1 , the element body 4 in this embodiment includes a first core portion 41 and a second core portion 42. The first core portion 41 and the second core portion 42 can be formed of a powder compact containing a magnetic material and a resin.
[0048] The magnetic material contained in each core 41, 42 can be composed of, for example, ferrite powder or metal magnetic powder. As ferrite powder, for example, Ni-Zn ferrite, Mn-Zn ferrite, etc. can be exemplified. In addition, as metal magnetic powder, there is no particular limitation, but for example, other soft magnetic alloys such as Fe-Ni alloy, Fe-Si alloy, Fe-Co alloy, Fe-Si-Cr alloy, Fe-Si-Al alloy, Fe-containing amorphous alloy, Fe-containing nanocrystalline alloy can be exemplified. In addition, auxiliary components can be appropriately added to the above-mentioned ferrite powder or metal magnetic powder.
[0049] Alternatively, the first core 41 and the second core 42 may be made of the same type of magnetic material, so that the relative magnetic permeability μ1 of the first core 41 and the relative magnetic permeability μ2 of the second core 42 are equal. Alternatively, the first core 41 and the second core 42 may be made of different magnetic materials.
[0050] In addition, for the magnetic material (i.e., ferrite powder or metal magnetic powder) constituting the first core portion 41 or the second core portion 42, the median particle size (D50) can be set to 5 μm to 50 μm. Moreover, the above-mentioned magnetic material can also be composed of a mixture of multiple particle groups with different D50s. For example, a large-diameter powder with a D50 of 8 μm to 15 μm, a medium-diameter powder with a D50 of 1 μm to 5 μm, and a small-diameter powder with a D50 of 0.3 μm to 0.9 μm can also be mixed.
[0051] When a plurality of particle groups are mixed as described above, there is no particular restriction on the ratio of large diameter powder, medium diameter powder and small diameter powder. In addition, the large diameter powder, medium diameter powder and small diameter powder can all be composed of the same type of material, or can be composed of different materials. In this way, by forming the magnetic material contained in the first core portion 41 or the second core portion 42 with a plurality of particle groups, the filling rate of the magnetic material contained in the element body 4 can be increased. As a result, the characteristics of the inductor 2, such as the eddy current loss of magnetic permeability or the DC superposition characteristics, are improved.
[0052] In addition, the particle size of the magnetic material can be measured by observing the cross section of the element body 4 by a scanning electron microscope (SEM) or a scanning transmission electron microscope (STEM), and analyzing the obtained cross-sectional photograph by software. At this time, the particle size of the magnetic material is preferably measured by converting the equivalent circle diameter.
[0053] In addition, when the first core 41 or the second core is formed by a metal magnetic powder, the particles constituting the powder are preferably insulated from each other. As an insulating method, for example, a method of forming an insulating film on the surface of the particles can be cited. As an insulating film, a film formed by a resin or an inorganic material, and an oxide film formed by oxidizing the surface of the particles by heat treatment can be cited. In the case of forming an insulating film by a resin or an inorganic material, as a resin, silicone resin, epoxy resin, etc. can be cited. As an inorganic material, phosphates such as magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, silicates such as sodium silicate (water glass), soda lime glass, borosilicate glass, lead glass, aluminosilicate glass, borate glass, sulfate glass, etc. can be cited. By forming an insulating film, the insulation between particles can be improved, and the withstand voltage of the inductor 2 can be improved.
[0054] In addition, there is no particular limitation on the resin contained in the first core portion 41 and the second core portion 42, but thermosetting resins such as epoxy resin, phenolic resin, melamine resin, urea-formaldehyde resin, furan resin, alkyd resin, polyester resin, diallyl phthalate resin, or thermoplastic resins such as acrylic resin, polyphenylene sulfide (PPS), polypropylene (PP), liquid crystal polymer (LCP), etc. can be used.
[0055] like Figure 1 As shown, the first core portion 41 has a flange portion 41a, a winding core portion 41b and a notch portion 41c. The flange portion 41a protrudes toward each side 4c~4f of the element body 4, and four flange portions 41a are formed correspondingly on each side 4c~4f. The coil portion 6α is mounted on the upper surface of the flange portion 41a, and the flange portion 41a supports the coil portion 6α. Here, the two flange portions 41a protruding along the X-axis direction are respectively set as the first flange portion 41ax, and the two flange portions 41a protruding along the Y-axis direction are respectively set as the second flange portion 41ay. The thickness of the first flange portion 41ax is thinner than the thickness of the second flange portion 41ay, and there is a space below the first flange portion 41ax to accommodate a part of the lead portion 6a.
[0056] The winding core 41b is located above the flange 41a in the Z-axis direction and is formed integrally with the flange 41a. The winding core 41b is formed of a substantially elliptical cylinder protruding upward in the Z-axis direction and is inserted into the inner side of the coil 6α. The shape of the winding core 41b is not limited to Figure 1 and Figure 3AThe illustrated form may be any shape as long as it matches the winding shape of the coil portion 6α, for example, a cylindrical shape or a prismatic shape.
[0057] The notch portion 41c is located between the flange portions 41a, and four notches are formed at the four corners of the XY plane. That is, the notch portion 41c is formed near the location where the side surfaces 4c to 4f of the element body 4 intersect with each other. The notch portion 41c is used as a passage for the lead portion 6a led out from the coil portion 6α to pass through. In addition, the notch portion 41c also serves as a passage for the molding material constituting the second core portion 42 to flow from the surface side to the back side of the first core portion 41 during the manufacturing process. Figure 1 In the embodiment, the notch 41c is cut into a substantially square shape, but as long as the shape allows the lead 6a and the molding material to pass through, there is no particular limitation. For example, the notch 41c may be a through hole that penetrates the front and back surfaces of the flange 41a.
[0058] like Figure 3A As shown, the second core portion 42 covers the first core portion 41. More specifically, the second core portion covers the coil portion 6α and the winding core portion 41b above the flange portion 41a, and fills the space existing below the notch portion 41c and the first flange portion 41ax. Figure 2 As shown, the lower surface of the second flange portion 41ay constitutes a part of the bottom surface 4b of the element body 4, and the second core portion 42 is not filled below the second flange portion 41ay.
[0059] like Figure 1 As shown, a pair of lead portions 6a are respectively led out from the coil portion 6α along the Y axis above the first flange portion 41ax. In addition, a pair of lead portions 6a are respectively folded back near the side 4c of the element body 4, and extend from the side 4c side to the side 4d side below the first flange portion 41ax.
[0060] Here, the height h in the Z-axis direction from the bottom surface 4b of the component body 4 to the first flange portion 41ax is smaller than the outer diameter of the lead portion 6a. Therefore, below the first flange portion 41ax, most of the lead portion 6a is accommodated inside the component body 4 (especially the second core portion 42), but a portion of the outer periphery of the lead portion 6a is exposed at the bottom surface 4b of the component body 4. The lead portion 6a is composed of the winding 6, but at the portion exposed at the bottom surface 4b, the insulating layer existing on the outer periphery of the winding 6 is removed to expose the conductor portion of the winding 6. In this embodiment, as shown in FIG. Figure 2 As shown in FIG. 1 , a portion of the bottom surface 4 b where the conductor portion of the winding 6 is exposed is particularly referred to as a lead electrode portion 61 .
[0061] In this embodiment, if Figure 2As shown, a pair of terminal electrodes 8 are formed so as to cover the pair of extraction electrode portions 61 , respectively, and the extraction electrode portions 61 and the terminal electrodes 8 are electrically connected.
[0062] The terminal electrode 8 has at least a resin electrode layer 81. In addition, the terminal electrode 8 may also be a laminated structure having the resin electrode layer 81 and other electrode layers. When the terminal electrode 8 is set as a laminated structure, the resin electrode layer 81 is located in the portion in contact with the lead-out electrode portion 61, and the other electrode layers are laminated on the outside of the resin electrode layer 81, that is, on the opposite side of the lead-out electrode portion 61. The other electrode layers may be a single layer or a multilayer, and their materials are not particularly limited. For example, the other electrode layers can be composed of metals such as Sn, Au, Ni, Pt, Ag, Pd, or alloys containing at least one of these metal elements, and can be formed by plating or sputtering. In addition, it is preferred that the overall average thickness of the terminal electrodes 8a and 8b is set to 10μm to 60μm, and it is preferred that the average thickness of the resin electrode layer 81 is set to 10μm to 20μm.
[0063] Figure 4A to Figure 4C 2 is a cross-sectional view showing an enlarged bonding boundary between the lead electrode portion 61 and the resin electrode layer 81 of the terminal electrode 8. Figure 4A As shown, the resin electrode layer 81 includes a resin component 82 and a conductor powder 83. The resin component 82 in the resin electrode layer 81 is composed of a thermosetting resin such as an epoxy resin or a phenolic resin. The conductor powder 83 mainly includes Ag, and may also include Cu, Ni, Sn, Au, Pd, etc.
[0064] In addition, in this embodiment, the conductive powder 83 of the resin electrode layer 81 is composed of two particle groups with different particle size distributions, namely, first particles 83a and second particles 83b. The first particles 83a are a particle group with a particle size of micrometer order. In this embodiment, "micrometer order particles" refer to particles with an average particle size of 0.05 μm or more and several tens of μm or less. Figure 4A In the cross section shown, the average particle size is preferably 1 μm to 10 μm, more preferably 3 μm to 5 μm.
[0065] In addition, the shape of the first particle 83a can be set to a shape close to a sphere, a prolate spheroid, an irregular block, a needle shape, or a flat shape, and a needle shape or a flat shape is particularly preferred. In this embodiment, the flat particle refers to a particle that is Figure 4A In the cross section shown in FIG. 1 , the aspect ratio (ratio of the length in the long side direction to the length in the short side direction) of the first particles 83a is 2 to 30. In addition, the average particle size of the first particles 83a can be determined by observing with SEM or STEM. Figure 4A to Figure 4CThe cross section shown in FIG. 1 is taken and the image analysis of the obtained cross-sectional photograph is performed to measure the average particle size of the first particles 83a. When performing this measurement, the average particle size of the first particles 83a is calculated by converting the maximum length.
[0066] On the other hand, the second particles 83b are a group of nanometer-level particles having an average particle size smaller than that of the first particles 83a. Figure 4B and Figure 4C As shown in FIG. 1 , the second particles 83b are present in agglomeration near the periphery of the first particles 83a or in the interparticle gaps of the first particles 83a. Figure 4C In the enlarged cross section shown in FIG. 1 , the second particle 83b is identified as an aggregate of microparticles having a particle size of at least 100 nm or less. In addition, the second particle 83b is added as nanoparticles having a roughly spherical shape and an average particle size (converted into an equivalent circle diameter) of 5 nm to 30 nm during the manufacturing process of the paste as the raw material of the resin electrode layer 81.
[0067] In addition, the first particles 83a and the second particles 83b described above both have Ag as their main component. When the conductive powder 83 also contains a metal element other than Ag, the presence of the metal element is not particularly limited. For example, the metal element other than Ag may exist as a particle other than the first particles 83a and the second particles 83b, or may be dissolved in the first particles 83a.
[0068] In addition, in Figure 4A In the cross section of the resin electrode layer 81 shown, if the area of the observation field including the resin component 82 and the conductor powder 83 is set to 100%, the area occupied by the conductor powder 83 is preferably 60% or more. In addition, in the cross section of the resin electrode layer 81, if the area occupied by the first particles 83a is set to A1 and the area occupied by the second particles 83b is set to A2, the ratio of A1 to A2 (A1 / A2) is preferably 1.5 to 6.0.
[0069] In addition, the area occupied by each element in the above can be observed by SEM or STEM. Figure 4A The cross section of the resin electrode layer 81 shown is measured by image analysis of the obtained cross-sectional image. When using SEM, it is preferred to observe with a reflected electron image, and when using STEM, it is preferred to observe with a HAADF image. In the above-mentioned observation image, the dark contrast portion is the resin component 82, and the bright contrast portion is the conductor powder 83. In addition, the second particle 83b is observed as an aggregate of tiny particles as described above, and the area A2 occupied by the second particle 83b is set as the area of its aggregate. In the above-mentioned observation, it is preferred to set the observation field of each field of view to 0.04μm 2 ~0.36μm 2It is preferred that the area occupied by each element is calculated as the average value of at least 10 observations of the field of view.
[0070] like Figure 4A As shown, at the interface between the lead-out electrode portion 61 and the resin electrode layer 81, with respect to the outermost surface of the lead-out electrode portion 61, there are a region R1 where the resin component 82 is in contact, a region R2 where the first particles 83a of the conductive powder 83 are in contact, and a region R3 where the second particles 83b of the conductive powder 83 are in contact. Figure 4A In the cross section shown, when the length of the boundary line between the extraction electrode portion 61 and the resin electrode layer 81 is set to 100%, the ratio of the region R3 in contact with the second particles 83 b is preferably about 20% to 100%.
[0071] In this embodiment, the diffusion layer 68 is formed at the interface between the lead electrode portion 61 and the resin electrode layer 81. Figure 4C As shown in FIG. 1 , the diffusion layer 68 is present in the region R3 where the second particles 83b are in contact with the outermost surface of the extraction electrode portion 61. Therefore, the diffusion layer 68 is present intermittently along the interface between the extraction electrode portion 61 and the resin electrode layer 81. Moreover, at the interface between the extraction electrode portion 61 and the resin electrode layer 81, the existence ratio of the diffusion layer 68 in the surface direction is equivalent to the ratio in the region R3 where the second particles 83b are in contact, and the existence ratio of the diffusion layer 68 in the surface direction increases as the content ratio of the second particles 83b contained in the resin electrode layer 81 increases.
[0072] The diffusion layer 68 contains at least copper oxide and Ag, and may also contain voids or a resin component 82. The diffusion layer 68 has a thickness T1 of at least 30 nm, preferably 30 nm to 500 nm, and more preferably 50 nm to 250 nm.
[0073] In addition, if Figure 4D As shown in FIG. 1 , there may be a region where an oxide film 61a mainly composed of copper oxide is formed on the surface side of the lead electrode portion 61. The oxide film 61a may be formed when the lead electrode portion 61 is exposed on the bottom surface 4b during the manufacturing process of the inductor 2. Alternatively, it may be formed by applying a resin electrode paste to the bottom surface 4b and performing a predetermined heat treatment. In addition, the oxide film 61a may be formed over the entire surface of the lead electrode portion 61, or may be formed only on a portion of the surface of the lead electrode portion 61.
[0074] In this embodiment, by exposing the extraction electrode portion 61 or forming the resin electrode layer 81 under the predetermined conditions described later, even if the oxide film 61a is formed, the diffusion layer 68 can be formed at the interface between the extraction electrode portion 61 and the resin electrode layer 81. In this case, the diffusion layer 68 is located between the oxide film 61a of the extraction electrode portion 61 and the resin electrode layer 81. In addition, the thickness T2 of the oxide film 61a can be set to about 5nm to 100nm, preferably in the range of 5nm to 30nm.
[0075] also, Figure 5A and Figure 5B This is a cross-sectional view of a resin electrode layer 811 formed of only particles 833 having a particle size of micrometers as in the conventional method. Figure 5A and Figure 5B In the case of the prior art shown, at the interface between the lead electrode portion 61 and the resin electrode layer 811, the particles 833 physically contact the lead electrode portion 61, thereby ensuring electrical contact between the lead electrode portion 61 and the terminal electrode 8. That is, when the conductive powder contained in the resin electrode layer 811 is composed of only micrometer-level particles 833, the diffusion layer 68 is not formed.
[0076] In this embodiment, the diffusion layer 68 is formed at the interface between the lead electrode portion 61 and the terminal electrode 8, so that the adhesion strength of the resin electrode layer 81 to the lead electrode portion 61 can be improved. As a result, the bonding reliability of the terminal electrode 8 to the element body 4 can be improved, and the resistance value of the terminal electrode 8 can be reduced.
[0077] As described above, the diffusion layer 68 contains copper oxide and Ag, but the presence or absence of the diffusion layer 68 can be identified by line analysis or mapping analysis using STEM-EPMA (electron beam microanalyzer).
[0078] For example, in the line analysis performed by STEM-EPMA, a measurement line is drawn in a direction substantially perpendicular to the interface between the lead-out electrode portion 61 and the resin electrode layer 81, and quantitative analysis is performed on the measurement line at a constant interval. In addition, when performing the above-mentioned analysis, the sample for STEM observation can be prepared by a microsampling method using a focused ion beam (FIB). In addition, in the online analysis, it is preferred to set the size (spot size) of each measurement point to a diameter of less than 1.5 nm, and it is preferred to set the interval between the measurement points to less than 1.0 nm.
[0079] Fig. 6A Schematic diagram showing the results of line analysis by EPMA along the measurement line VIA. Fig. 6AAs shown, a concentration gradient of Ag is generated within a range of thickness T1 from the outermost surface of the extraction electrode portion 61 toward the resin electrode layer 81. Here, the outermost surface of the extraction electrode portion 61 can be identified from the observation image of the STEM, but it can also be identified based on the Cu content. Specifically, the position where the Cu content begins to decrease is set as the outermost surface of the extraction electrode portion 61. Moreover, in the present embodiment, the region where the concentration gradient of Ag is generated from the outermost surface of the extraction electrode portion 61 toward the resin electrode layer 81 side is specified as the diffusion layer 68. More specifically, the region where the Ag content tends to increase while changing from the outermost surface of the extraction electrode portion 61 toward the resin electrode layer 81 side is set as the diffusion layer 68.
[0080] In addition, if the outermost surface side of the extraction electrode portion 61 is defined as the starting point of the diffusion layer 68 on the measurement line VIA, the end point of the diffusion layer 68 is defined as the position where the Ag content is stable.
[0081] Furthermore, in the case where the oxide film 61a exists on the surface side of the extraction electrode portion 61, the following is obtained: Figure 6B The line analysis results are shown. Figure 6B In the graph of FIG. 1 , there is a region where the Cu content is reduced and oxygen is detected on the surface side of the extraction electrode portion 61. In the present embodiment, the region where the oxygen content is 3 wt % or more on the surface side of the extraction electrode portion 61 is determined to be the oxide film 61a. In addition, when the oxide film 61a exists, the "outermost surface of the extraction electrode portion 61" is set to the position where the Cu content is reduced and the oxygen content begins to decrease.
[0082] In addition, in line analysis by EPMA, elements present in the depth direction of the measurement point or elements present near the outer periphery of the measurement point affect the component analysis results. Figure 5B In the absence of the diffusion layer 68, a region where a slight but visibly Ag concentration gradient occurs may exist at the interface between the lead electrode portion 61 and the resin electrode layer 811. Figure 7 is the line analysis result when there is no diffusion layer 68. In this embodiment, Figure 7 As shown in FIG. 1 , when the thickness of the region B where the Ag concentration gradient is observed is less than 30 nm, it is determined that the diffusion layer 68 does not exist.
[0083] In addition, when it is difficult to identify the diffusion layer 68 only by the concentration gradient of Ag, the diffusion layer 68 is also identified in combination with the concentration gradient of Cu. Fig. 6AAs shown, a concentration gradient of Cu is also generated in the range of thickness T1 from the outermost surface of the extraction electrode portion 61 toward the resin electrode layer 81. That is, there is a tendency that the content of Cu changes and decreases from the outermost surface of the extraction electrode portion 61 toward the resin electrode layer 81. The diffusion layer 68 is set as a region where the concentration gradient of Ag and the concentration gradient of Cu are repeatedly generated from the outermost surface of the extraction electrode portion 61 toward the resin electrode layer 81. Even when the diffusion layer 68 is identified in this way, its thickness T1 is at least 30nm or more. When it is less than 30nm, it is determined that the diffusion layer 68 does not exist.
[0084] Furthermore, the diffusion layer 68 may be specified based on the following definition in addition to the above-mentioned method. That is, the diffusion layer 68 is a region on the resin electrode layer 81 side of the outermost surface of the lead-out electrode portion 61, where both the Ag content and the Cu content are 5 wt% or more. Alternatively, the diffusion layer 68 is a region where the Ag content varies within the range of 5 wt% to 100 wt% and the Cu content varies within the range of 5 wt% to 100 wt%.
[0085] On the other hand, in the case of measuring the diffusion layer 68 by mapping analysis using STEM-EPMA, the following results are obtained: Figure 8A to Figure 8C Mapping image shown. Fig. 8A is the mapping image of Ag, Figure 8B is the mapping image of Cu, Figure 8C is the mapping image of O. In addition, Figure 8A to Figure 8C In the figure, the center is the diffusion layer 68, the right side in the figure is the extraction electrode portion 61, and the left side in the figure is the resin electrode layer 81.
[0086] Comparing the mapping images of each element (Ag, Cu, O), it can be seen that in the diffusion layer 68, there are areas where Cu and O overlap. It can also be seen that Cu and O exist in the parts where the detection amount of Ag is small, and the areas where Cu and O overlap exist in the grain boundaries of Ag particles. That is, the Cu component contained in the diffusion layer 68 does not exist as pure copper or Ag-Cu alloy, but exists as copper oxide. Moreover, the copper oxide of the diffusion layer 68 exists in the grain boundaries of Ag particles.
[0087] As described above, when mapping analysis is performed on the interface between the extraction electrode portion 61 and the resin electrode layer 81 , the diffusion layer 68 can be recognized as a portion where Ag particles and copper oxide are mixed.
[0088] Next, a method for manufacturing the inductor 2 according to the present embodiment will be described.
[0089] First, the first core 41 is made by an extrusion method such as heat and pressure molding, or an injection molding method. In the production of the first core 41, raw material powder of the magnetic material, a binder, a solvent, etc. are kneaded to form particles, and the particles are used as raw materials for molding. In the case where the magnetic material is composed of multiple particle groups, magnetic powders with different particle size distributions are prepared and mixed at a specified ratio.
[0090] Next, the coil portion 6α is mounted on the obtained first core portion 41. The coil portion 6α is an air-core coil in which the winding wire 6 is pre-wound into a predetermined shape, and the air-core coil is inserted into the winding core portion 41b of the first core portion 41. Alternatively, the winding wire 6 may be directly wound around the winding core portion 41b of the first core portion 41 to form the coil portion 6α. After the first core portion 41 and the coil portion 6α are combined, as shown in FIG. Figure 1 As shown in FIG. 1 , a pair of lead wire portions 6a are led out from the coil portion 6α and are arranged below the first flange portion 41ax.
[0091] Next, the second core portion 42 is made by insert injection molding. In the making of the second core portion 42, first, the first core portion 41 equipped with the coil portion 6α is arranged inside the molding die. Preferably, the inner surface of the molding die is pre-paved with a demoulding film. As a demoulding film, a flexible sheet-like member such as a PET film can be used. By using a demoulding film, when the first core portion 41 is arranged in the molding die, the lead portion 6 located below the first flange portion 41ax is in close contact with the demoulding film. As a result, a portion of the outer periphery of the lead portion 6a is covered by the demoulding film, and after the making of the second core portion 42, a portion of the outer periphery of the lead portion 6a is exposed from the bottom surface 4b of the element body 4.
[0092] As the raw material constituting the second core portion 42, a material having fluidity during molding can be used. Specifically, a composite material formed by mixing raw material powder of a magnetic material with an adhesive such as a thermoplastic resin or a thermosetting resin is used. A solvent, a dispersant, etc. may also be appropriately added to the composite material. In insert injection molding, the above-mentioned composite material is introduced into a molding mold in a slurry state. At this time, the introduced slurry passes through the notch portion 41c of the first core portion 41 and is also filled to the bottom of the first flange portion 41ax. In addition, during injection molding, heating is appropriately performed according to the material of the adhesive used. Accordingly, an element body 4 in which the first core portion 41, the second core portion 42, and the coil portion 6α are integrated is obtained.
[0093] Next, at a portion of the bottom surface 4b of the element body 4, that is, at Figure 2The portion where a pair of terminal electrodes 8 are formed is irradiated with laser to form the electrode predetermined portion. By this laser irradiation, the insulating layer of the lead portion 6a exposed on the bottom surface 4b is removed, and the lead electrode portion 61 is formed. In addition, by laser irradiation, the resin contained in the core portions 41 and 42 is removed on the outermost surface of the bottom surface 4b. That is, in the electrode predetermined portion, the magnetic material contained in the core portions 41 and 42 is exposed, and the lead electrode portion 61 is exposed. As a result, the terminal electrode 8 is easily in close contact with the bottom surface 4b of the element body 4.
[0094] The laser used in the above is preferably a short-wavelength UV laser with a wavelength of less than 400nm. In laser processing, green laser (wavelength 532nm) is generally used, but the principles of removing the object (insulating layer of the lead part 6a or resin of the core, etc.) are different between green laser and UV laser. In the case of green laser, the surface temperature of the object rises sharply due to the irradiation of laser, and the object melts or evaporates (thermal decomposition), thereby removing the object. Therefore, if green laser is used, it is easy to form an oxide film with a thickness of more than 100nm on the surface of the exposed lead electrode part 61, inhibiting the formation of the diffusion layer 68. On the other hand, in the case of UV laser, UV laser removes the object by decomposing the molecular bonds of the organic compound constituting the object. Even if a slight temperature rise is generated and thermal decomposition occurs when using UV laser, it is much more difficult to form an oxide film than when using green laser. Therefore, by using UV laser, it is easy to form a diffusion layer 68.
[0095] In addition, as the method for forming the electrode predetermined portion, mechanical grinding, blasting treatment, chemical corrosion treatment, etc. can also be considered, but these methods can also easily form a film (oxide film or corrosion layer) with a thickness exceeding 100nm. Therefore, the electrode predetermined portion is preferably formed by irradiation of UV laser as described above.
[0096] Next, the resin electrode paste is applied to the predetermined portion of the electrode by printing or other methods. The resin electrode paste used at this time contains a binder that becomes the resin component 82, and a metal raw material powder that becomes the conductor powder 83. More specifically, the metal raw material powder is composed of microparticles with a particle size of micrometer order and nanoparticles with a particle size of nanometer order. The microparticles are particles that become the first particles 83a after the paste is solidified, and the average particle size is preferably 1μm to 10μm, and more preferably 3μm to 5μm. On the other hand, the nanoparticles are particles that become the second particles 83b after the paste is solidified, and the average particle size is preferably 5nm to 30nm, and more preferably 5nm to 15nm.
[0097] In the printing of the resin electrode paste, the coating amount and other conditions are controlled so that the average thickness of the resin electrode layer 81 after the heat treatment is 10 μm to 20 μm. By adjusting the thickness of the resin electrode layer 81 to the above range, the diffusion layer 68 is easily formed.
[0098] After the resin electrode paste is applied to the electrode predetermined portion, the element body 4 is heated under predetermined conditions to solidify the binder (resin component 82) in the paste. The heat treatment conditions are preferably such that the treatment temperature (maintaining temperature) is set to 170° C. to 230° C. and the holding time is set to 60 min to 90 min. By performing the heat treatment under such conditions, a resin electrode layer 81 is formed on the electrode predetermined portion of the element body 4.
[0099] Here, the method for forming the diffusion layer 68 is described. In the present embodiment, it is conceivable that the diffusion layer 68 is formed by the following steps: 1) after forming the predetermined electrode portion by UV laser irradiation, 2) applying a resin electrode paste containing nanoparticles to the predetermined electrode portion with a predetermined thickness (the thickness of the resin electrode layer 81 after heat treatment becomes a thickness of 10 to 20 μm), 3) performing heat treatment under prescribed conditions. In addition, the thickness T1 of the diffusion layer 68 can be controlled by the conditions during the heat treatment. For example, when performing the heat treatment, there is a tendency that the more heat energy is input (increasing the holding temperature or extending the holding time), the thicker the thickness T1 of the diffusion layer 68. In addition, the above-mentioned conditions for forming the diffusion layer 68 are only examples, and sometimes the diffusion layer 68 can be formed under conditions other than those described above.
[0100] After forming the resin electrode layer 81, a plating film or a sputtering film may be appropriately formed on the outer surface of the resin electrode layer 81. For example, by forming a plating film of Ni, Cu, Sn, etc. on the outer surface of the resin electrode layer 81, wettability to solder is improved.
[0101] By the above-described manufacturing method, the inductor 2 is obtained in which the pair of terminal electrodes 8 are formed on the element body 4 .
[0102] (Summary of the First Embodiment)
[0103] In the inductor 2 of the present embodiment, the terminal electrode 8 has a resin electrode layer 81. The resin electrode layer 81 is formed by curing the resin component 82, and does not require a high-temperature sintering process during the manufacturing process. In addition, in the inductor 2 of the present embodiment, a diffusion layer 68 containing Ag and copper oxide is formed at the interface between the lead electrode portion 61 and the resin electrode layer 81. By forming the diffusion layer 68, the adhesion strength of the resin electrode layer 81 to the lead electrode portion 61 can be improved. As a result, the bonding reliability of the terminal electrode 8 is improved, and the resistance value of the terminal electrode 8 can be reduced.
[0104] In addition, in the present embodiment, the conductor powder 83 of the resin electrode layer 81 is composed of the second particles 83b made of nanoparticles and the first particles 83a with a flat shape and a particle size of micrometers. By setting such a structure, the adhesion strength of the resin electrode layer 81 relative to the lead-out electrode portion 61 is further improved, and the bonding reliability of the terminal electrode 8 is further improved. In addition, by having the above-mentioned structure, the second particles 83b agglomerate in the interparticle gaps of the first particles 83a, and play a role in electrically connecting the first particles 83a. As a result, the resistance value of the terminal electrode 8 can be further reduced.
[0105] In addition, in the present embodiment, an oxide film 61a may be formed on at least a portion of the surface of the lead electrode portion 61. Even if the oxide film 61a is present, the diffusion layer 68 can be formed by forming the resin electrode layer 81 under the above-mentioned conditions. Therefore, even in the presence of the oxide film 61a, the bonding reliability of the terminal electrode 8 is improved, and the resistance value of the terminal electrode 8 can be reduced.
[0106] The embodiments of the present invention have been described above, but the present invention is not limited to the above-mentioned embodiments, and various changes can be made within the scope of the present invention. Figure 1 to Figure 3A In the embodiment, the coil portion 6α is composed of a winding wire 6 of a round wire, but the type of the winding wire 6 is not limited thereto and may also be Figure 3B The cross-sectional shape of the conductor portion shown is a substantially rectangular flat wire. Alternatively, it may be a quadrilateral or a stranded wire formed by twisting thin wires. Furthermore, the coil portion 6α may be formed by stacking conductive plates.
[0107] In the above embodiment, the terminal electrode 8 is formed on the bottom surface 4b of the element body 4, but the terminal electrode 8 is not limited thereto and may be formed on the top surface 4a or the side surfaces 4c to 4f or may be formed across multiple surfaces.
[0108] The conductive powder 83 of the resin electrode layer 81 may be composed only of the second particles 83b made of nanoparticles. Alternatively, particles having a larger specific surface area than the fine particles (first particles 83a) may be used instead of the second particles 83b.
[0109] In addition, the first core portion 41 constituting the element body 4 can be set as a sintered body of ferrite powder or metal magnetic powder. In addition, the element body 4 itself can also be set as a FT type, ET type, EI type, UU type, EE type, EER type, UI type, drum type, bottle type, cup type pressed powder core or sintered body core, and a coil is wound on the core to form an inductor element. In this case, the lead portion does not need to be buried inside the element body, and can also be led out along the outer periphery of the core and connected to the outer surface of the terminal electrode 8.
[0110] In addition, the electronic component of the present invention is not limited to an inductor, and may be an electronic component such as a capacitor, a transformer, a choke coil, a common mode filter, etc. For example, when the electronic component is a laminated ceramic capacitor, the portion of the internal electrode layer included in the laminated body that is exposed at the end surface of the laminated body is the lead electrode portion 61. In addition, in the laminated ceramic capacitor, the terminal electrode 8 is formed on the end surface of the laminated body in accordance with the exposed portion of the internal electrode layer.
[0111] Example
[0112] Hereinafter, the present invention will be further described based on detailed examples, but the present invention is not limited to these examples.
[0113] Example
[0114] In an embodiment, making Figure 1 The inductor sample shown. Specifically, an element body having an electrode predetermined portion is produced by the method described in the embodiment, and a resin electrode layer with a thickness of 10 to 20 μm is formed in the electrode predetermined portion. When forming the resin electrode layer, a resin electrode paste containing flat first particles (Ag microparticles) and second particles (Ag nanoparticles) is used, and a heat treatment is performed under the conditions described in the embodiment. Moreover, for the obtained inductor sample, the interface between the lead electrode portion and the terminal electrode is analyzed by STEM-EPMA (line analysis). As a result, in the embodiment, compared with Fig. 6A Similar to the graph of , it can be confirmed that a diffusion layer is formed at the interface between the extraction electrode portion and the resin electrode layer (particularly, a portion where the aggregates of the second particles are in contact with each other), and the thickness T1 of the diffusion layer is 120 nm.
[0115] Comparative Example
[0116] In the comparative example, a resin electrode paste containing only Ag particles was used as the conductor powder to produce an inductor sample. In addition, for the comparative example, the interface between the lead electrode portion and the terminal electrode was analyzed by STEM-EPMA. Figure 7 The same analysis results confirmed that no diffusion layer was formed.
[0117] evaluate
[0118] The DC resistance of the inductor sample obtained above and the contact resistance of the terminal electrode were measured. For the embodiment and the comparative example, ten DC resistances and contact resistances were measured respectively, and their average values and CV values (coefficient of variation) were calculated. As a result, in the embodiment with a diffusion layer, it can be confirmed that the contact resistance is reduced by 4% compared with the comparative example. In addition, in the embodiment and the comparative example, the CV value of the DC resistance is compared. In the embodiment, the CV value is about 1 / 3 of that of the comparative example. According to the results, by forming a diffusion layer on the interface between the lead-out electrode portion and the terminal electrode, the resistance value of the terminal electrode can be reduced, and the deviation of the resistance value can also be reduced.
[0119] In addition, in order to confirm the bonding reliability of the terminal electrodes, a high temperature load test (accelerated test) was implemented. In the high temperature load test, the inductor sample was exposed to a high temperature environment of more than 100°C for a long time while a voltage was applied to it, and the rate of increase of the DC resistance after exposure was measured. As a result, in the embodiment, the rate of increase of the DC resistance after the test was suppressed to less than 1 / 2 of that of the comparative example. Based on this result, it can be confirmed that the bonding reliability of the terminal electrodes is improved by forming a diffusion layer.
[0120] Explanation of symbols
[0121] 2…Inductor
[0122] 4……Component body
[0123] 4a...upper surface
[0124] 4b... bottom
[0125] 4c~4f……side view
[0126] 41……First core
[0127] 41a: flange
[0128] 41b……Core
[0129] 41c……Notch
[0130] 42... Second core
[0131] 6α…Coil part
[0132] 6. Winding
[0133] 6a……Lead wire
[0134] 61……Leading electrode part
[0135] 61a……Oxide coating
[0136] 8……Terminal electrode
[0137] 81……Resin electrode layer
[0138] 82……Resin composition
[0139] 83... Conductor powder
[0140] 83a...the first particle
[0141] 83b…the second particle
[0142] 68...Diffusion layer
Claims
1. An electronic component, wherein: have: The lead-out electrode portion is provided on the outer surface of the element body; as well as a resin electrode layer formed on a portion of the outer surface of the element body and connected to the lead-out electrode portion; The lead electrode portion is a metal containing copper as a main component, The resin electrode layer comprises a silver-containing conductor powder and a resin, The conductive powder of the resin electrode layer is composed of first particles having a particle size of micrometer order and second particles having a particle size of nanometer order. A diffusion layer containing copper oxide and silver is formed at the interface between the resin electrode layer and the extraction electrode portion. At the interface, relative to the outermost surface of the extraction electrode portion, there are a first region in contact with the resin component in the resin electrode layer, a second region in contact with the first particles, and a third region in contact with the second particles. The diffusion layer exists in the third region, and is intermittently formed along the interface.
2. The electronic component according to claim 1, wherein The diffusion layer has a thickness of at least 30 nm.
3. The electronic component according to claim 2, wherein: In the diffusion layer, a silver concentration gradient is generated from the outermost surface of the extraction electrode portion toward the resin electrode layer side.
4. The electronic component according to any one of claims 1 to 3, wherein The first particle is flat. The second particles are aggregated between the first particles.
5. The electronic component according to any one of claims 1 to 4, wherein An oxide film mainly containing copper oxide is formed on the surface side of the extraction electrode portion. The diffusion layer is located between the oxide film and the resin electrode layer.
Citation Information
Patent Citations
Conductive resin paste and laminated ceramic chip capacitor with terminal electrode consisting of same
JP1994267784A
Electrode formation method of electronic component
JP2013045926A
Coil component, method of manufacturing the same, and electronic device
CN105321685A
Electronic device and its production
JP1999345745A
Electronic component
JP2018006501A